Inclusion and release of ant alarm pheromones from metal–organic frameworks. Issue 30 (21st July 2020) - Amer Hamzah, Harina; Rixson, Daniel; Paul-Taylor, Joseph; Doan, Huan V.; Dadswell, Christopher; Roffe, Gavin W.; Sridhar, Arun; Hobday, Claire L.; Wedd, Charlie; Düren, Tina; Hughes, William O. H.; Spencer, John; et al.
Abstract : Zinc(ii ) and zirconium(iv ) MOFs show uptake and slow release of the ant alarm pheromones 3-octanone and 4-methyl-3-heptanone. Abstract : Zinc(ii ) and zirconium(iv ) metal–organic frameworks show uptake and slow release of the ant alarm pheromones 3-octanone and 4-methyl-3-heptanone. Inclusion of N -propyl groups on the MOFs allows for enhanced uptake and release over several months. In preliminary field trials, leaf cutting ants show normal behavioural responses to the released pheromones.